Healthcare Providers’ Perspectives on Barriers and Needs in Delivering Perinatal Mental Health Services - Padmaningtyas, Dewi Anggraini; Hidayat, Asri; Mamnuah, Mamnuah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Healthcare providers’ perspectives on barriers and needs in delivering perinatal mental health services are crucial, as they play a central role in identifying and managing perinatal mental health problems and are often the first point of contact for women experiencing such conditions. This review aimed to describe healthcare providers’ views on the challenges and requirements in providing perinatal mental health services. A scoping review design was employed, drawing data from PubMed, ScienceDirect, EBSCO, and Google Scholar. The included articles were original research studies published in English or Indonesian within the last five years (2019–2024). The search terms included healthcare worker, healthcare professional, healthcare provider, barrier, need, challenge, perinatal mental, health service, and maternal mental health care. The findings from 15 relevant articles indicated that barriers to perinatal mental health services include limited awareness, insufficient knowledge and skills, cultural beliefs and stigma, inadequate resources and infrastructure, and poor communication. Identified needs encompassed enhanced training and resource allocation, public awareness campaigns, and the development of clear policies and guidelines. In conclusion, perinatal mental health services across various countries highlight substantial barriers and needs from the perspective of healthcare providers. Integrating mental health into routine maternal care and strengthening interdisciplinary collaboration may improve outcomes for both mothers and infants.Keywords: barriers; needs; healthcare providers; mental health; perinatal